Pengaruh Penerapan Prinsip Etika Bisnis Islam Terhadap Kepuasan Konsumen Di Swalayan Al-Baik Kota Tanjungpinang Provinsi Kepulauan Riau - Kencara, Pamela Kenia; Rahman, Aulia (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
This study aims to determine the effect of the Application of Islamic Business Ethics Principles on Customer Satisfaction at Al-Baik Supermarket in Tanjungpinang City, Riau Islands Province. The population of this study were consumers who shopped at Al-Baik Supermarket for the last 2 months as many as 66,000 with the number of samples studied 100 respondents. Collecting data for this study using a questionnaire method. The analysis technique using SPSS Version 25 includes instrument analysis in the form of validity and reliability analysis. The results of the validity analysis showed that all 26 statement items were proven valid, while the results of the reliability analysis showed that the Cronbach's Alpha value 0.6 was declared reliable. Data analysis includes classical assumption tests and simple regression tests. The results of the classical assumption test showed that the normality test was normally distributed and the heteroscedasticity test did not detect heteroscedasticity. The simple regression test research results show that the coefficient of determination (R Square) is 0.415 or 41.5%. The t test shows that the tcount is 8.342 and ttable is 1.984 with a significance value of 0.000 0.05. The F test shows that the value of Fcount = 69.583 with a significance value of 0.000 0.05, it can be concluded that there is an influence of the variable application of Islamic business ethics principles on the variable customer satisfaction.